The Use Of Paperless Learning Media In Efl Classroom: A Qualitative Study About The Use Of Paperless Learning Media In English Subject At Stimikom Stella Maris Sumba - Emirensiana Dappa Ege; Dian Fransiska Ledi; Derniati Malo; Stanislaus Dedelis Adat; Desti Mariana Taklal (Qalam : Jurnal Ilmu Kependidikan, 2023)
English subject is one of the important subject at Stimikom Stella Maris. This international languawge is able to deliver students to international networks. To support the class, the media that usews in learning process not only modules but also paperless.This study reports the use of paperless learning media in STIMIKOM Stella Maris Sumba. In the informatics management study program, there are four classes. Each class has twenty students. The English course is given in the first and second of semester. This research uses a qualitative descriptive method with data collection techniques are interview, observation and documentation. The results of this study indicates that the paperless learning media in English subject class is beneficial to both the student and lecturer. Keywords: paperless learning media, English Subject